The strengths and weaknesses of viscoelastic testing compared to traditional coagulation testing. (22nd October 2020) - Cohen, Tobias; Haas, Thorsten; Cushing, Melissa M.
Abstract: Optimized acute bleeding management requires timely and reliable laboratory testing to detect and diagnose coagulopathies and guide transfusion therapy. Conventional coagulation tests (CCT) are inexpensive with minimal labor requirements, but CCTs may have delayed turnaround times. In addition, abnormal CCT values may not reflect in vivo coagulopathies that require treatment and may lead to overtransfusion. The use of viscoelastic testing (VET) has been rapidly expanding and is recommended by several recent bleeding guidelines. This review is intended to compare CCT to VET, review the strengths and weaknesses of both approaches, and evaluate and summarize the clinical studies that compared CCT‐based and VET‐based transfusion algorithms. Most studies of CCT vs VET transfusion algorithms favor the use of VET in the management of massively bleeding patients due to reductions in blood product utilization, bleeding, costs, and lengths of stay.